Awareness of Green Marketing and its Influence on Buying Behavior of Consumers: Special Reference to Durable Goods - Singh, Simranjit; Soniya (Gyan Management Journal, 2018)
Global warming, pollution and climate change are some of the problems that have become increasingly concerning issue internationally. Environmental deterioration has led to businesses changing the way in which they conduct themselves, leading to the emergence of green marketing. This Rising concern for global warming & corresponding increase in energy costs are causing consumer’s to look for those products which are environment friendly. There has been a change in consumer attitudes towards lifestyle. Today most of the consumers have become environment conscious and the main challenge is to find a way how marketing can fulfill the needs of the most of the world’s population for a better standard of living. To grasp the new emerging opportunities and to ensure better standard of living, the new concept -Green Marketing has emerged. Green Marketing promotes marketing of such products which are safer for the planet & people. This changing attitude of buying behaviour is forcing many firms to incorporate green processes. In this small research serve it is revealed that Indian consumers’ pro-environmental concerns, knowledge of environmental issues, awareness of eco-friendly products, and educational levels affect on green buying behavior.